2012
DOI: 10.1002/adhm.201200125
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method to Precisely Assemble Loose Nanofiber Structures for Regenerative Medicine Applications

Abstract: Polymer nanofibers are favorable for tissue engineering scaffolds because of their high surface-to-volume ratio and biomimicry of the extracellular matrix. Random and uniaxially oriented polymer nanofibers are easily fabricated by conventional electrospinning techniques; however, control over fiber organization within nanofiber structures is limited when they are collected directly from an electrospinning jet. The regenerative medicine applications of electrospun scaffolds could be expanded by developing assem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 22 publications
0
29
0
Order By: Relevance
“…The versatility of electrospun fiber sheets in mimicking extracellular matrix (ECM) [20-23] and the benefits of high surface-to-volume ratio fibrous matrices for cell attachment, drug loading, and mass transport [24, 25] enable the construction of a flexible tissue membrane that can fit bone of any size and shape. To overcome the limitations of nanofibrous sheets in cellular infiltration and vascular ingrowth, we further adopted a layer-by-layer assembly strategy [26], which has been successfully used in a number of tissue engineering applications to facilitate uniform cell seeding and complex tissue construction [27-32]. …”
Section: Introductionmentioning
confidence: 99%
“…The versatility of electrospun fiber sheets in mimicking extracellular matrix (ECM) [20-23] and the benefits of high surface-to-volume ratio fibrous matrices for cell attachment, drug loading, and mass transport [24, 25] enable the construction of a flexible tissue membrane that can fit bone of any size and shape. To overcome the limitations of nanofibrous sheets in cellular infiltration and vascular ingrowth, we further adopted a layer-by-layer assembly strategy [26], which has been successfully used in a number of tissue engineering applications to facilitate uniform cell seeding and complex tissue construction [27-32]. …”
Section: Introductionmentioning
confidence: 99%
“…Generally, nonwoven polymer fibrous scaffolds are made with spinning techniques either using polymer solutions or melts . The primary focus of the spinning technique is the production of fibers in a scale range from nano‐ to microrange that resembles the native extracellular matrix (ECM) . Although there has been much research on solution spinning to form fibrous polymer scaffolds for tissue engineering and wound healing applications, little has been reported on melt spinning to fabricate nonwoven scaffolds .…”
Section: Introductionmentioning
confidence: 99%
“…The author emphasizes, that the successful fabrication of the electrospun nanofibrous scaffolds starts with the selection of proper polymers, whereas the combination of multiple polymers as well as various postmodification techniques may provide desirable properties [12] . Beachley and coworkers addressed the limited control over fiber organization within nanofiber structures when they are collected directly from an electrospinning jet [13] . Furthermore, a novel assembly technique that utilizes parallel automated tracks to orient and collect nanofibers from the electrospinning jet has been established in order to allow a better control of the fiber organization, resulting in a continuous steady-state delivery of static stabilized nanofibers [13] .…”
Section: Methods For Nanofiber Synthesismentioning
confidence: 99%
“…Beachley and coworkers addressed the limited control over fiber organization within nanofiber structures when they are collected directly from an electrospinning jet [13] . Furthermore, a novel assembly technique that utilizes parallel automated tracks to orient and collect nanofibers from the electrospinning jet has been established in order to allow a better control of the fiber organization, resulting in a continuous steady-state delivery of static stabilized nanofibers [13] . Another study by Leverson and colleagues demonstrated the feasibility of fabrication of electrospun scaffolds containing two differently scaled fibers as well as scaffolds containing fibers of the two different materials fibrin and PCL using a dual extrusion electrospinning setup.…”
Section: Methods For Nanofiber Synthesismentioning
confidence: 99%